Micro-nano three-level structure coating resistant to CMAS thermal shock and preparation method of micro-nano three-level structure coating

By preparing the PtNiAl metal bonding layer, YSZ and GYbZ ceramic layers on the high-temperature alloy matrix and carrying out femtosecond laser processing to form a micro-grid structure, the damage problem of the thermal barrier coating under the thermal shock of CMAS is solved, and significant improvement in thermal shock resistance and wear performance are achieved.

CN119876947APending Publication Date: 2025-04-25BEIHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510001821.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing thermal barrier coatings are susceptible to thermal shock and wear from CMAS particles at high temperatures, resulting in coating damage and aircraft engine safety threats.

Method used

The metal bonding layer was prepared by electroplating Pt aluminized process, and the YSZ and GYbZ ceramic layers were prepared on it by plasma physical vapor deposition. Finally, femtosecond laser processing was performed on the surface of the ceramic layer to form a regular arrangement of microgrid structure.

Benefits of technology

It significantly improves the anti-CMAS thermal shock and wear performance of the coating, extends the thermal shock life of high-temperature gas, and improves the anti-friction performance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876947A_ABST
    Figure CN119876947A_ABST
Patent Text Reader

Abstract

The invention provides a CMAS thermal shock resistant micro-nano three-level structure coating and a preparation method thereof. The preparation method of the coating comprises the following steps: firstly, carrying out surface pretreatment on the high-temperature alloy matrix, and then preparing the PtNiAl metal bonding layer on the high-temperature alloy matrix by adopting electroplating Pt aluminizing; the preparation method comprises the following steps: firstly, preparing a metal bonding layer, then preparing double ceramic layers on the metal bonding layer by adopting plasma physical vapor deposition, and finally, carrying out femtosecond laser processing on the surfaces of the ceramic layers to enable the surfaces of the ceramic layers to present a regularly arranged micro-grid structure. The coating provided by the invention has relatively low elastic modulus, better friction and wear resistance and excellent high-temperature gas and CMAS coupling thermal shock resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal barrier coatings, and in particular to a micro-nano three-level structure coating resistant to CMAS thermal shock and a preparation method thereof. Background Art

[0002] The aircraft engine is the "heart" of the aircraft and the power of high-end national defense equipment such as ships, rockets, and missiles. High thrust-to-weight ratio is the eternal pursuit of high-performance aircraft engines. As the thrust-to-weight ratio increases, the engine turbine inlet temperature is also constantly increasing. Therefore, it is necessary to coat the surface of the high-temperature alloy with a thermal barrier coating for thermal protection. There are fine silicate particles in the air, which mainly come from the atmospheric environment, volcanoes, and dust. They are composed of CaO, MgO, Al2O3 and SiO2, referred to as CMAS. During the service process at high temperatures, the thermal barrier coating will frequently be eroded by high-temperature and high-speed CMAS particles, resulting in foreign body damage to the coating, posing a serious threat to the service life of the thermal barrier coating and the safety of aircraft engines. Therefore, the thermal barrier coating is required to have good mechanical properties, especially the ability to resist the thermal shock of CMAS particles. Summary of the invention

[0003] In order to solve the above problems, the present invention provides a micro-nano three-level structure coating resistant to CMAS thermal shock and wear and a preparation method thereof.

[0004] According to a first aspect, the present invention provides a method for preparing a micro-nano three-level structure coating resistant to CMAS thermal shock and wear, comprising the following steps:

[0005] S0, high temperature alloy substrate surface pretreatment.

[0006] S1. Using a Pt electroplating and aluminum infiltration process, a PtNiAl metal bonding layer is prepared on the high-temperature alloy substrate.

[0007] S2. Using plasma physical vapor deposition, a ceramic layer is prepared on the metal bonding layer, wherein the ceramic layer includes a YSZ layer located on the inner side and a GYbZ layer located on the outer side.

[0008] S3. Perform femtosecond laser processing on the surface of the ceramic layer to make the surface of the ceramic layer present a regularly arranged micro-grid structure.

[0009] The femtosecond laser processing process parameters include: the laser is scanned along two mutually perpendicular directions, the distance between two adjacent laser beam processing tracks is 10 to 80 μm, the laser power P is 5 to 20 W, and the scanning times are 5 to 20 times.

[0010] In some embodiments, the surface pretreatment includes sandblasting, and the sandblasting parameters are: pressure 0.2 MPa, wet blasting, time 2 min.

[0011] In some embodiments, in S1, the Pt electroplating process parameters are: temperature 95°C, main salt is dinitrosodiammine platinum, current density is 1ASD, pH value is 10-10.5, deposition efficiency is 5-6μm / h, time is 30-40min, and a Pt layer with a thickness of 3μm is obtained; after Pt electroplating, the sample is heat treated at 1050°C for 2h.

[0012] In some embodiments, in S1, the aluminum infiltration process parameters are: the infiltrant includes an iron-aluminum alloy powder containing 49 wt.% iron and NH4Cl powder, the temperature is 1070°C, and the insulation time is 6 hours.

[0013] In some embodiments, the YSZ layer has a thickness of 50 μm, and the GYbZ layer has a thickness of 200-250 μm.

[0014] In some embodiments, in S2, the plasma physical vapor deposition process parameters are: plasma beam net power 20kW~65kW, substrate temperature 800~900°C, spraying distance 800~1200mm, argon gas flow rate 15~40L / min, and powder feeding rate 10~20g / min.

[0015] In some embodiments, in S3, the femtosecond laser processing parameters also include: a pulse time of 209 fs, a central wavelength of 1030 nm, a frequency of 80 to 120 kHz, and a scanning speed of 5 to 30 mm / s.

[0016] According to the second aspect, the present invention provides a micro-nano tertiary structure coating resistant to CMAS thermal shock and wear, characterized in that it is prepared by any one of the preparation methods in the first aspect.

[0017] In some embodiments, the coating surface presents a micro-nano tertiary structure: the primary structure is a "micrometer cone protrusion" formed by laser processing, the secondary structure is a "cauliflower head" columnar crystal structure prepared by PS-PVD, and the tertiary structure is nanoparticles formed during the processing.

[0018] The coating provided by the present invention has a lower elastic modulus and more excellent anti-friction and wear performance, and at the same time, the high-temperature fuel gas thermal shock life under the CMAS coupling effect is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0020] Figure 1 One of the surface morphology images of a micro-nano three-level structure coating provided in an embodiment of the present invention;

[0021] Figure 2 The second surface morphology image of a micro-nano three-level structure coating provided in an embodiment of the present invention is the secondary structure described in the text;

[0022] Figure 3 The third surface morphology diagram of a micro-nano three-level structure coating provided in an embodiment of the present invention is the three-level structure described in the text;

[0023] Figure 4 A surface macroscopic morphology of a coating provided as a comparative example of the present invention under the thermal shock of gas without CMAS coupling;

[0024] Figure 5 A surface macroscopic morphology of a coating provided in an embodiment of the present invention under the thermal shock of gas without CMAS coupling;

[0025] Figure 6 A surface macroscopic morphology of a coating provided as a comparative example of the present invention after 1250 times of gas thermal shock under CMAS coupling;

[0026] Figure 7 A surface macroscopic morphology of a coating provided in the comparative example of the present invention after 2220 times of gas thermal shock under CMAS coupling;

[0027] Figure 8 A surface macroscopic morphology of a coating provided in an embodiment of the present invention after 2500 times of gas thermal shock under CMAS coupling. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be described below in conjunction with the accompanying drawings.

[0029] The present invention aims to obtain a thermal barrier coating with excellent mechanical properties, anti-friction and wear properties, and excellent resistance to high-temperature gas thermal shock under CMAS coupling. From the perspective of material selection, yttria-stabilized zirconia (YSZ) ceramic material has excellent comprehensive properties below 1200°C, such as high thermal expansion coefficient, high stress-strain tolerance, good high-temperature phase stability and high fracture toughness. In addition, Yb-modified gadolinium zirconate material (GYbZ), as a new type of thermal barrier coating material, not only has excellent resistance to CMAS corrosion, but also has extremely low thermal conductivity at high temperatures, with a thermal conductivity of only 0.8 W·m at 1600°C. -1 K -1Therefore, YSZ and GYbZ are selected as thermal barrier coating ceramic insulation layer materials.

[0030] Traditional coating preparation technologies include atmospheric plasma spraying (APS) and electron beam physical vapor deposition (EB-PVD) technology. The APS coating has a layered structure and good thermal insulation performance, but poor bonding strength and poor thermal cycle life; the thermal cycle life of the coating prepared by EB-PVD has been improved, but there are problems such as poor thermal insulation performance and low deposition efficiency. At present, the quasi-columnar structure coating prepared by the new coating preparation technology plasma physical vapor deposition (PS-PVD) technology has better thermal insulation performance and high-temperature gas impact performance. However, under the engine service environment, the quasi-columnar structure coating prepared by PS-PVD will cause structural degradation due to high-temperature sintering, and the high-temperature service life will decrease. Therefore, the present invention adopts the PS-PVD method to prepare a thermal barrier coating ceramic insulation layer, and the coating is surface modified by ultrafast laser to prepare a micro-nano tertiary structure coating, and improve the high-temperature stability of the coating.

[0031] The coating preparation method provided by the present invention is described below in conjunction with specific embodiments.

[0032] Example

[0033] A micro-nano three-level structure coating is prepared on the surface of an IC21 single crystal high-temperature alloy substrate to resist thermal shock and wear of high-temperature gas under CMAS coupling. The specific steps include:

[0034] S0, high temperature alloy substrate surface pretreatment.

[0035] This embodiment uses IC21 single crystal high temperature alloy as the substrate, and performs sandblasting on the surface of the IC21 single crystal high temperature alloy substrate with a diameter of 32 mm. The sandblasting parameters are: pressure 0.2 MPa, wet spraying 2 minutes.

[0036] S1. Using a Pt electroplating and aluminum infiltration process, a PtNiAl metal bonding layer is prepared on the high-temperature alloy substrate.

[0037] The following introduces the Pt electroplating process and the aluminum infiltration process in the Pt electroplating aluminum infiltration process respectively.

[0038] Electroplating Pt: After the sandblasted IC21 single crystal high temperature alloy substrate is ultrasonically cleaned, it is placed in the Pt electroplating solution. The electroplating time is 30-40 minutes, the temperature is 95°C, the main salt is dinitrosodiammine platinum, the current density is 1ASD, the pH value is 10-10.5, the deposition efficiency is 5-6μm / h, the time is 30-40 minutes, and a Pt layer with a thickness of 3μm is obtained. The sample is then placed in a vacuum heat treatment furnace for 2 hours of heat treatment, and the temperature is set to 1050°C.

[0039] Aluminizing: Next, a mixed powder of iron-aluminum alloy powder (Fe content 49 wt.%) and NH4Cl was used as a penetrant for vapor phase aluminizing. The aluminizing temperature was 1070°C and the holding time was 6 hours.

[0040] Thus, the preparation of the PtNiAl metal bonding layer is completed. Next, a ceramic layer is prepared on the bonding layer.

[0041] S2. Using plasma physical vapor deposition, a ceramic layer is prepared on the metal bonding layer, wherein the ceramic layer includes a YSZ layer located on the inner side and a GYbZ layer located on the outer side.

[0042] The plasma physical vapor deposition process parameters are: plasma beam net power 20kW ~ 65kW, substrate temperature 800 ~ 900 ℃, spraying distance 800 ~ 1200mm, argon flow rate 15 ~ 40L / min, powder feeding rate 10 ~ 20g / min. First, a 50μm YSZ layer is prepared on the metal bonding layer, and then a 200 ~ 250μm GYbZ layer is prepared on it. During the preparation process, an atomic infrared emission spectrometer (OES, PLASCALC-2000) is used to monitor the equipment in real time, mainly monitoring the degree of powder vaporization and the properties of the plasma jet during the spraying process, and an infrared camera and thermocouple are used to monitor the substrate temperature.

[0043] S3. Perform femtosecond laser processing on the surface of the ceramic layer to make the surface of the ceramic layer present a regularly arranged micro-grid structure.

[0044] The prepared PtNiAl / YSZ / GYbZ thermal barrier coating sample was placed on a high-precision computerized XY translation platform, and a high-speed scanning galvanometer was used to scan the laser along two mutually perpendicular directions to remove the material and form a regularly arranged micro-grid structure on the sample surface. The scanning spacing Δz was set to 10 to 80 μm to achieve micro-grid structure processing with different groove spacings.

[0045] The femtosecond laser processing parameters are: laser power P is 20W, scanning times are 5 to 20 times, pulse time is 209fs, central wavelength is 1030nm, frequency is 80 to 120kHz, and scanning speed is 5 to 30mm / s.

[0046] The above is combined with the embodiments to introduce the coating preparation method provided by the present invention. The following is combined with the accompanying drawings to specifically introduce the micro-nano three-level structure thermal barrier coating prepared in the embodiment and its properties to reflect the advantages of the present invention.

[0047] Figure 1 , Figure 2 and Figure 3 The surface morphology of a micro-nano three-level structure thermal barrier coating provided by an embodiment of the present invention at different magnifications. It can be seen that the ceramic layer surface is processed by femtosecond laser, so that the ceramic layer surface presents a regular micro-grid structure, which together with the micro-nano composite bionic structure prepared by PS-PVD forms a micro-nano three-level structure. The primary structure is the "micrometer cone protrusion" ( Figure 1 ), the secondary structure is the "cauliflower head" columnar crystal structure prepared by PS-PVD ( Figure 2 ), the tertiary structure is the nanoparticles formed during the processing ( Figure 3 ), the three levels together form a micro-nano three-level structure.

[0048] It should be noted that in the coating preparation method provided by the present invention, PS-PVD and femtosecond laser processing must be combined to obtain a micro-nano three-level structure coating with excellent resistance to high-temperature gas thermal shock performance due to CMAS coupling, and femtosecond laser processing plays a vital role and is indispensable. In this regard, this specification also provides relevant comparative examples and experimental data, as follows:

[0049] In the comparative example, a PS-PVD "micro-nano composite bionic structure" thermal barrier coating was prepared, which differed from the preparation process of the embodiment only in that the femtosecond laser processing step on the surface of the ceramic layer was removed.

[0050] The surface macroscopic morphology of the comparative example (i.e., PS-PVD "micro-nano composite bionic structure" coating) and the embodiment (i.e., the ultrafast laser processed "micro-nano tertiary structure" coating provided by the present invention) is shown in FIG. Figure 4 and Figure 5 The high temperature gas thermal shock performance of the coating samples of the above embodiment and the comparative example under the coupling effect of CMAS was compared and studied.

[0051] Under different gas thermal shock times, the surface macroscopic morphology of the coating obtained in the comparative example is shown in Figure 6 ,and Figure 7 As shown; the macroscopic morphology of the coating surface obtained in the embodiment is shown Figure 8As shown. It can be seen that after 1250 times of CMAS coupled gas thermal shock, local peeling has occurred in the center of the coating; after 2220 times, the coating peeling area exceeds 20%, and the coating is completely ineffective. However, after 2500 times of high-temperature gas thermal shock, the micro-nano three-level structure coating modified by ultrafast laser surface remains relatively intact, proving that the structure coating has a gas thermal shock resistance life of more than 2500 times, and the coating has excellent resistance to molten CMAS thermal shock.

[0052] Combining the CMAS-coupled high-temperature gas thermal shock experiments of the embodiment and the comparative example, it can be seen that the thermal cycle life of the thermal barrier coating ceramic surface after laser processing is higher than that of the coating without laser processing, which proves that the micro-nano three-level structure coating provided by the present invention has better resistance to CMAS-coupled high-temperature gas thermal shock.

[0053] In the description of the embodiments of the present application, words such as "exemplary", "for example" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary", "for example" or "for example" in the embodiments of the present application should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary", "for example" or "for example" is intended to present related concepts in a concrete way.

[0054] In the description of the embodiments of the present application, the term "and / or" is merely a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists alone, B exists alone, and A and B exist at the same time. In addition, unless otherwise specified, the term "plurality" means two or more.

[0055] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. The terms "include", "comprises", "has" and their variations all mean "including but not limited to", unless otherwise specifically emphasized.

[0056] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made on the basis of the technical solution of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a micro-nano three-level structure coating resistant to CMAS thermal shock, characterized in that: The following steps are involved: S0, high temperature alloy substrate surface pretreatment; S1, using a Pt electroplating aluminum infiltration process to prepare a PtNiAl metal bonding layer on the high-temperature alloy substrate; S2. Using plasma physical vapor deposition to prepare a ceramic layer on the metal bonding layer, the ceramic layer includes a YSZ layer located on the inner side and a GYbZ layer located on the outer side; S3, performing femtosecond laser processing on the surface of the ceramic layer, so that the surface of the ceramic layer presents a regularly arranged micro-grid structure; The femtosecond laser processing process parameters include: the laser is scanned along two mutually perpendicular directions, the distance between two adjacent laser beam processing tracks is 10 to 80 μm, the laser power P is 5 to 20 W, and the scanning times are 5 to 20 times.

2. The coating preparation method according to claim 1, characterized in that: The surface pretreatment includes sandblasting, and the sandblasting parameters are: pressure 0.2 MPa, wet blasting, time 2 minutes.

3. The coating preparation method according to claim 1, characterized in that: In S1, the process parameters for electroplating Pt are: temperature 95°C, main salt is dinitrosodiammine platinum, current density is 1ASD, pH value is 10-10.5, deposition efficiency is 5-6μm / h, time is 30-40min, and a Pt layer with a thickness of 3μm is obtained; after electroplating Pt, the sample is heat treated at 1050°C for 2h.

4. The coating preparation method according to claim 3, characterized in that: In S1, the aluminum infiltration process parameters are: the infiltrant includes iron-aluminum alloy powder containing 49 wt.% of iron and NH4Cl powder, the temperature is 1070°C, and the insulation time is 6 hours.

5. The coating preparation method according to claim 1, characterized in that: The thickness of the YSZ layer is 50 μm, and the thickness of the GYbZ layer is 200-250 μm.

6. The coating preparation method according to claim 1, characterized in that: In S2, the plasma physical vapor deposition process parameters are: plasma beam net power 20kW-65kW, substrate temperature 800-900°C, spraying distance 800-1200mm, argon gas flow rate 15-40L / min, and powder feeding rate 10-20g / min.

7. The coating preparation method according to claim 1, characterized in that: In S3, the femtosecond laser processing parameters also include: pulse time of 209 fs, central wavelength of 1030 nm, frequency of 80-120 kHz, and scanning speed of 5-30 mm / s.

8. A micro-nano three-level structure coating resistant to CMAS thermal shock, characterized in that: The preparation method is described in any one of claims 1 to 7.

9. The coating according to claim 8, characterized in that The coating surface presents a micro-nano three-level structure: the primary structure is the "micrometer cone protrusions" formed by laser processing, the secondary structure is the "cauliflower head" columnar crystal structure prepared by PS-PVD, and the tertiary structure is the nanoparticles formed during the processing.